Study of Mud Clam Polymesoda erosa (Bivalvia) Conservation Strategy Based on Landscape Character and Anthropogenic Activity - Anang Kadarsah; Krisdianto Krisdianto; Ika Oksi Susilawati (UIN Sunan Gunung Djati Bandung, 2018)
Information on landscape character and anthropogenic activity is necessary to develop conservation strategy, especially for mud clam (Polymesoda erosa) sustainability harvesting. The purpose of this study is to identify the landscape character and anthropogenic activity that influence mud clam conservation strategy in the coast of Tabanio Village, Takisung Sub-District in Tanah Laut Regency. The research discovered seven types of landscape in the coastal area of Tabanio namely human settlements, rice fields, plantations, cemetery abandoned land, offices, and other public infrastructures. Landscape, landscaping, abandoned land and settlements provide the largest contribution (96 %t) in the formation of coastal characters. Related to changes in landscape structure, environmental pollution activity in the form of waste disposal to the landscape is the most frequent activity (91.4 %) related to changes in landscape structure. Destructing collecting, cutting down and destroying plants and animals in and from the region (87.7%) are the most frequent anthropogenic activities related to the conservation of mud clam in the coast of Tabanio Village. The landscape zonation consists of four i.e : recreation zone, mangrove forest zone, economic zone and distribution zone. The position of each zone tends to clump primarily for the economic zone behind the recreation zone. The core zone of the landscape design at Tabanio Coast , Takisung District is concentrated in the recreation zone which functions as a meeting place for various communities (fishermen, traders and visitors) and the government workers (village officials and TNI-Polri). Furthermore, the recreation zone also facilitates activities that support coastal economy and tourism. Community assistance programs are required to build the capacity of fishermen and farmers as an effort to achieve a successful mud clam conservation and management in Tabanio Village, Takisung District.